Interactions between Hedgehog proteins and their binding partners come into view. - Beachy, P; Hymowitz, S; Lazarus, R; Leahy, D; Siebold, C (2010)
Hedgehog (Hh) proteins are secreted signaling molecules that mediate essential tissue-patterning events during embryonic development and function in tissue homeostasis and regeneration throughout life. Hh signaling is regulated by multiple mechanisms, including covalent lipid modification of the Hh protein and interactions with multiple protein and glycan partners. Unraveling the nature and effects of these interactions has proven challenging, but recent structural and biophysical studies of Hh proteins and active fragments of heparin, Ihog, Cdo, Boc, Hedgehog-interacting protein (Hhip), Patched (Ptc), and the monoclonal antibody 5E1 have added a new level of molecular detail to our understanding of how Hh signal response and distribution are regulated within tissues. We review these results and discuss their implications for understanding Hh signaling in normal and disease states.